The Underrepresentation of Women in Science: International and Cross-Disciplinary Evidence and Debate - Stephen J. Ceci (Frontiers Research Topics, 2018)
There is no shortage of articles and books exploring women's underrepresentation in science. Everyone is interested--academics, politicians, parents, high school girls (and boys), women in search of college majors, administrators working to accommodate women's educational interests; the list goes on. But one thing often missing is an evidence-based examination of the problem, uninfluenced by personal opinions, accounts of "lived experiences," anecdotes, and the always-encroaching inputs of popular culture. This is why this special issue of Frontiers in Psychology can make a difference. In it, a diverse group of authors and researchers with even more diverse viewpoints find themselves united by their empirical, objective approaches to understanding women's underrepresentation in science today. The questions considered within this special issue span academic disciplines, methods, levels of analysis, and nature of analysis; what these article share is their scholarly, evidence-based approach to understanding a key issue of our time.